About Hummingbirds a guide for children /\ - Sill, Cathryn P.; Sill, John (Atlanta, GA Peachtree, 2011)
Covers basic facts about hummingbird life and some of the different species of hummingbirds.
Keywords: Hummingbirds; JUVENILE NONFICTION / Animals / Birds; JUVENILE NONFICTION / Science & Nature / Biology; Juvenile works